A nuclear factor kappa B reporter cell line used to evaluate ex vivo the net inflammatory effect of plasma samples from patients with rheumatoid arthritis, psoriasis, or COVID-19. (February 2021) - Wagner, Lelia; Haefeli, Walter E.; Merle, Uta; Lorenz, Hanns-Martin; Hohmann, Nicolas; Weiss, Johanna; Theile, Dirk
Graphical abstract: Highlights: A NF-κB reporter cell line to analyze plasma of patients with rheumatoid arthritis, psoriasis, or COVID-19. C-reactive protein associates with enhanced NF-κB activity. COVID-19 plasma enhances NF-κB in reporter cells, samples from rheumatoid arthritis or psoriasis do not. Abstract: Background: The overall clinical outcome of inflammatory conditions is the result of the balance between pro-inflammatory and anti-inflammatory mediators. Because nuclear factor kappa B (NF-ĸB) is at the bottom of many inflammatory conditions, methods to evaluate the net effect of inflammation modulators on this master regulator have been conceptualized for years. Methods: Using an ex vivo NF-ĸB reporter cell line-based assay, plasma samples of patients with rheumatoid arthritis (n = 27), psoriasis (n = 15), or severe coronavirus disease-19 (COVID-19) (n = 21) were investigated for NF-ĸB activation compared to plasma samples from 9 healthy volunteers. Results: When separated by C-reactive protein (CRP) threshold levels, samples of patients exhibiting increased CRP levels (≥5 mg/l) activated NF-ĸB more efficiently than samples from patients with levels below 5 mg/l (P = 0.0001) or healthy controls (P = 0.04). Overall, there was a moderate association of CRP levels with NF-ĸB activation (Spearman r = 0.66; p < 0.0001). Plasma from COVID-19 patients activated NF-ĸB more efficiently (mean 2.4-fold compared to untreated reporter cells) than samples from any other condition (healthy controls, 1.8-fold, P = 0.0025; rheumatoid arthritis, 1.7-fold, P < 0.0001; psoriasis, 1.7-fold, P < 0.0001). In contrast, effects of rheumatoid arthritis, psoriasis, or healthy volunteer samples did not differ. Conclusion: This study shows that a NF-ĸB reporter cell line can be used to evaluate the net inflammatory effect of clinical plasma samples. Patients with chronic but stable rheumatoid arthritis or psoriasis do not exhibit increased plasma levels of NF-ĸB-activating compounds as opposed to COVID-19 patients with high inflammatory burden.